Microwave-hydrothermal synthesis of Y3Fe3.35Al1.65O12 nanoparticles for magneto-hyperthermia application - Borsari, E. [UNESP]; Freire, B. G.G. [UNESP]; Garcia, F. G.; Silva, M. S.; Silva, C. C. [UNESP]; Simões, A. Z. [UNESP] (Springer Nature, 2018)
Crystalline aluminum substituted yttrium iron garnet nanoparticles Y3Fe3.35Al1.65O12 (YIG) was synthesized by hydrothermal microwave synthesis at 140 °C with soaking times ranging from 15 to 60 min. X-ray diffraction confirmed the single-phase YIG nanoparticles excluding the presence of any other phases in the reaction products. The Raman spectra revealed that the largest soaking time provides greater energy crystallization causing changes of lattice vibration and a certain degree of disorder in the crystal lattice. Field emission gun-scanning electron microscopy and high resolution transmission electronic microscopic revealed a homogeneous size distribution of nanometric YIG powders with agglomerated particles. Magnetic measurements were achieved by using a vibrating-sample magnetometer unit. YIG nanoparticles have great potential in magneto-hyperthermia application once in vivo applications magnetic induction heating ferromagnetic compounds generate heat in AC magnetic fields.